Artificial Intelligence and the Sociology of Folklore: A Comparative Study of Turkey and Indonesia - Dewi Christa Kobis; Michel Farrel Tomatala (JOMLAI: Journal of Machine Learning and Artificial Intelligence, 2025)
This study examines how Artificial Intelligence (AI) mediates the production and circulation of folklore in Turkey and Indonesia and asks: How does AI mediate folklore production and circulation in both contexts? And What similarities and differences characterize AI–folklore interaction from a sociological perspective? Using a qualitative comparative cultural sociology design, the analysis draws on Turkish sociological theory, Ziya Gokalp’s concept of halk kültürü and Şerif Mardin’s center–periphery framework alongside documentary and digital ethnographic observation of publicly accessible folklore texts, AI-mediated outputs (retellings, translations, summaries), and platform-based circulation. Findings show that AI mediates folklore production through textual regeneration, translation, narrative standardization, and platform-oriented adaptation, while circulation is shaped by recommendation, tagging, ranking, and translation interfaces that regulate visibility, dissemination, and the dominance of particular versions. Although both countries experience algorithmic pressures on cultural memory and narrative visibility, impacts diverge by context: Turkey’s institutionally anchored cultural authority tends to constrain AI toward selective continuity, whereas Indonesia’s pluralistic and decentralized landscape allows AI and platforms to operate as stronger cultural gatekeepers, enabling more transformative reinterpretations. Overall, the study concludes that AI is a structural cultural mediator whose sociological effects are context-dependent, amplifying existing power relations rather than uniformly transforming folklore.